China : How Can Revenue Reforms Contribute to Inclusive and Sustainable Growth? - Lam, Waikei (IMF Working Papers; Working Paper ;, 2015)
Revenue reforms can contribute to more inclusive, green, and sustainable growth in China. Relative to OECD economies, fiscal policy in China is less redistributive. Options for promoting more inclusive growth include improving the progressivity of labor taxes (individual income tax and social security contributions), introducing a recurrent property tax, and finishing the transition to a comprehensive value-added tax. Higher environmental taxes, meanwhile, would promote more environment-friendly economy. These reforms could also significantly boost revenue, potentially by as much as 6 1\2 percent of GDP. Such increases in revenue could help reduce the deficit, finance priority social and infrastructure spending, and offset cuts in other taxes. We illustrate how these revenue reforms could be part of a comprehensive fiscal package that achieves the needed consolidation in the (augmented) deficit and foster higher quality growth.